2012
DOI: 10.5402/2012/806792
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Built Environment on Mental and Sexual Health: Policy Implications and Recommendations

Abstract: Research related to the intersection of the built environment and health has particularly flourished in the last decade. The authors highlight the theoretical and policy insights that have been made while also noting paucity in this literature as specifically related to mental and sexual health. Overall, the authors discuss policy implications of aspects of the built environment on both mental and sexual health behaviors and outcomes and suggest avenues for future research, program implementation, and policyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The built environment refers to the physical structures that people live in and around, as well as the neighborhood environment [ 88 ]. " Riskscapes " describe geographic areas with low incomes and an excess of poor land use, neighborhood stressors, and limited access to healthcare resources or healthy land uses such as parks and open spaces [ 88 ].…”
Section: The Built Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The built environment refers to the physical structures that people live in and around, as well as the neighborhood environment [ 88 ]. " Riskscapes " describe geographic areas with low incomes and an excess of poor land use, neighborhood stressors, and limited access to healthcare resources or healthy land uses such as parks and open spaces [ 88 ].…”
Section: The Built Environmentmentioning
confidence: 99%
“…The built environment refers to the physical structures that people live in and around, as well as the neighborhood environment [ 88 ]. " Riskscapes " describe geographic areas with low incomes and an excess of poor land use, neighborhood stressors, and limited access to healthcare resources or healthy land uses such as parks and open spaces [ 88 ]. Research into the effect of the built environment has found that adolescent residents of riskscapes have higher rates of sexually transmitted infections (STIs) , unprotected sexual activities, and unintended pregnancies [ 88 ].…”
Section: The Built Environmentmentioning
confidence: 99%
See 3 more Smart Citations